The therapeutic effects of white kwao krua pueraria mirifica airy shaw and suvatabandhu on ovariectomy - induced osteoporotic rats - Somrudee Hanmanop (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2010